2021
DOI: 10.9744/jti.22.1.17-24
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Usage of E-Wallet among the Y Generation in Surabaya based on Technology Acceptance Model

Abstract: Although the government of Indonesia is building the cashless society, the number of e-wallet users are increasing slowly. E-wallet is becoming a common instru­ment of payments from the paper-based instruments to server-based electronic money. The aim of this research is to investigate the perceived usage of the Y Genera­tions on e-wallet based on Technological Acceptance Model (TAM) which is a power­ful model to describe single approval to the usage of a new information technology system. As a quantitative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 23 publications
11
39
0
2
Order By: Relevance
“…The results of this study are similar to the study of (Pertiwi et al, 2020) which confirms that the intention to use digital wallets is positively and significantly influenced by perceived usability. In this study, it is known that the perceived usefulness has attracted the public's intention to switch to the non-cash transaction method.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this study are similar to the study of (Pertiwi et al, 2020) which confirms that the intention to use digital wallets is positively and significantly influenced by perceived usability. In this study, it is known that the perceived usefulness has attracted the public's intention to switch to the non-cash transaction method.…”
Section: Discussionsupporting
confidence: 87%
“…Recent study concluded that PU positively influences that attitude and intentions of users in mobile wallet context (Chawla and Joshi, 2019). In this view, earlier studies posited that the intention to use mobile payment services is positively influenced by PU (Routray et al, 2019;Routray, 2019;Pertiwi et al, 2020;Jin, 2020). Hence, based on these arguments, it can be hypothesized that: H1.…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 94%
“…The TAM model is highly recognized and used in new technological innovation studies (Pertiwi et al, 2020) and is considered as a theoretically robust model to identify the determinants of intentions to new technology (Abdullah et al, 2016;Nunes et al, 2018). Recent studies have used TAM to predict the intentions to use mobile wallets technology (Lew et al, 2020;Singh et al, 2020).…”
Section: Theoretical Background and Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…An energy efficiency intention is a form of desire to be wise and efficient when consuming energy. Previous research found that energy efficiency intention has a positive and significant effect on energy-saving behaviour [42,43,44]; the higher the intention, the higher the saving energy behaviour [45,46]. This has informed analysis of the millennial generation's energy efficiency intention on their behaviour in an eco-friendly home and the formulation of the hypothesis H5: H5: Energy efficiency intention has a positive and significant effect on the millennial energy efficiency behaviour in an eco-friendly home.…”
Section: Energy Efficiency Intention and Behaviourmentioning
confidence: 98%